Turritopsis fascicularis Fraser, 1943 (Cnidaria: Hydrozoa): redescription and discussion of its phylogenetic position within the genus - Miglietta, Maria Pia (Zootaxa, 2016)
Turritopsis fascicularis Fraser, 1943 was first described off Alligator Reef, Florida, USA, at a depth of 216 m. Presumably a deep-sea species, its validity has often been questioned due to the scarcity of available records. In this paper, T. fascicularis is re-described from some mature colonies from the upper slope of the Gulf of Mexico. Furthermore, new pictures of the colony, polyps, and medusa buds, are provided. A ~600bp sequence of the large ribosomal subunit of the mitochondrial RNA (lsu-rRNA, 16S), also known as the Hydrozoan barcoding molecule, is used for the first time to confirm the validity of T. fascicularis as a species, and analyze its phylogenetic position within the genus Turritopsis.